A Systematic Review of Photolysis and Hydrolysis Degradation Modes, Degradation Mechanisms, and Identification Methods of Pesticides. (6th June 2022) - Meng, Xingang; Guo, Yuanjun; Wang, Yihui; Fan, Shijun; Wang, Kaiqi; Han, Wenhua
Abstract : The degradation modes and characteristics of different pesticides were introduced. In addition, this paper also describes the degradation mechanism of different pesticides, classifies, and summarizes the methods of degradation products identification. For the sake of human life health and better biological environment, we should have a familiar knowledge of the natural degradation of pesticides and understand the photo-hydrolysis and its influencing factors (temperature, pH, light, etc.). Through the degradation mechanism and influencing factors, the degradation time could be accelerated and it also provides a theoretical basis and basic support for the treatment of pesticide residues in the future.